Itchy rash in pregnancy - Abdul Hadi, Azwanis; Jamani, Nurjasmine Aida; Ismail, Mohd Nizamuddin (Faculty of Medicine, University Teknologi Mara, 2022)
A 30-year-old gravida 3 para 2 with a twin pregnancy at 35 weeks period of gestation complained of intensely itchy rash for the past 4 days. The rash started as tiny papules on her abdomen. The papules increased in numbers and spread to her umbilical area, breasts and inner forearms. There were no other rash or itchiness elsewhere. She had no underlying personal or family history of atopic disease. She had not applied any creams on her abdomen or had taken any oral medications. Otherwise, her antenatal period was uneventful. On examination, there were multilple papules with some coalescing forming plaques at the distensae area on her abdomen, breasts, and inner forearms. There were some excoriation marks but no vesicles or blisters were seen. Generally, the periumbilical region was spared.